Representatives Illocutionary Acts by the Main Character Found in Fast X Movie - Ni Made Jelianti; I Made Yogi Marantika (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
This study aimed to analyzing illocutionary acts found in Fast X movie. This study entitled